2006
DOI: 10.1108/17410400610710206
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable continuous improvement methodology at an aerospace company

Abstract: Purpose -The purpose of this paper is to present a continuous improvement methodology developed in an aerospace company that is successfully being used by other companies in various industries. Design/methodology/approach -A case study was undertaken at a medium-sized aerospace company for over a span of one year. Data was collected through in-depth interviews, attendance at formal and informal meetings, observation, and company documentation. Findings -The paper provides an overview of a continuous improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 6 publications
2
74
0
15
Order By: Relevance
“…Some examples of theoretical studies are Bhuiyan et al (2006), Suárez-Barraza (2008), Suárez-Barraza et al (2011), Singh and Singh (2009, 2012 or Dahlgaard-Park et al (2013). However, among the analysed studies we have not found papers that, combining qualitative and quantitative analysis, review the evolution of the continuous improvement field.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Some examples of theoretical studies are Bhuiyan et al (2006), Suárez-Barraza (2008), Suárez-Barraza et al (2011), Singh and Singh (2009, 2012 or Dahlgaard-Park et al (2013). However, among the analysed studies we have not found papers that, combining qualitative and quantitative analysis, review the evolution of the continuous improvement field.…”
Section: Introductionmentioning
confidence: 82%
“…(Chang, 2005) The continuous improvement cycle consists of establishing customer requirements, meeting the requirements, measuring success, and continuing to check customers' requirements to find areas in which improvements can be made. (Bhuiyan, Baghel, & Wilson, 2006) Culture of sustained improvement aimed at eliminating waste in all organizational systems and processes, and involving all organizational participants. (Manos, 2007) Subtle and gradual improvements that are made over time.…”
Section: Limitationsmentioning
confidence: 99%
“…O Lean Manufacturing é caracterizado pela ênfase na manutenção de um fluxo contínuo ao longo dos processos produtivos, de modo a prover flexibilidade à produção em se adaptar às flutuações na demanda (BHUIYAN;BAGHEL, 2005 Refugo; Após identificar os desperdícios e eliminá-los, a nova organização começa a produzir itens com mais qualidade e um custo baixo, além de ser mais flexível no mix de produto e reduzir seus tempos de produção (ANDERSSON, R.; ERIKSSON, H.; TORSTENSSON, 2006;.…”
Section: Revisão Bibliográficaunclassified
“…Há uma variedade de empresas que têm experimentado as vantagens da aplicação dessa metodologia nas suas áreas de fabricação. A Boeing, por exemplo, por meio da aplicação dos conceitos da Produção Enxuta, eliminou grande parte de suas atividades que não agregavam valor aos seus produtos e os tornou mais competitivos, via redução de custo (BHUIYAN;BAGHEL, 2005;CHEN;COX, 2012).…”
Section: Introductionunclassified
“…(Liker, 2006). (Bhuiyan et al, 2006) stated that lean production was one of the oldest improvement methodologies, providing high value to the customer by using of best practices such as Kanban, mistake proofing and 5S. Many authors have demonstrated on how and when used appropriately, lean philosophy can help to eliminate the waste in process industry, maintain better inventory control, increase and improve product quality and reduced operational costs and materials.…”
Section: In the Bookmentioning
confidence: 99%